(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article intends to present the experience of indigenous aesthetic practices, especially from the Tepi Platform (Theatre and Indigenous Peoples). The production of Tepi Podcast emerged from a partnership between Podcast Paraskeué and Tepi, making up the idea of how the podcast can be an instrument for recording the speeches and ways of doing things of indigenous artists, at the same time, in which we have the rise of digital platforms as powerful instruments for indigenous presence in the virtual environment.